Participation in the labour market of woman in Hungary in European context - Szabó, Katalin (Studia Mundi – Economica, 2017)
In this paper, I analyse women’s labour market participation in Hungary in European context. The results are based on Eurostat and Hungarian Central Statistics Office databases. Relative to the other member states of the EU woman’s employment remains low in Hungary since economic and political transformation. Differences between male and female participation rates have narrowed now days in our country, but discrimination of women is reflected in some areas.